Innowacyjność a kultura gospodarcza gmin - Polski, Jan (Innovativeness in the Economic Culture of Communities, 2008)
Innovativeness is one of the main priorities in the policy of the EU and Poland. The article indicates the importance of development of innovations, not only in technological sphere but also in the sphere of organization. Apart from companies and science institutes, territorial, regional and local self-governments should also become important animators of innovative development. Their mandate is to create facilities for innovations, for instance by supporting development of economic culture. Both spheres support each other and together they can have more effective influence on development of cities, rural communities and regions. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 154-163